Echocardiographic parameters in athletes of different sports - Venckunas, T.; Lionikas, A.; Marcinkeviciene, J. E.; Raugaliene, R.; Alekrinskis, A.; Stasiulis, A. (Journal of Sports Science & Medicine, 2008)
Competitive athletics is often associated with moderate left ventricular (LV) hypertrophy, and it has been hypothesized that training mode and type of exercise modulates long-term cardiac adaptation. The purpose of the study was to compare cardiac structure and function among athletes of various sports and sedentary controls. Standard transthoracic two-dimensional M-mode and Doppler echocardiography was performed at rest in Caucasian male canoe/kayak paddlers (n = 9), long distance runners (LDR, n = 18), middle distance runners (MDR, n = 17), basketball players (BP, n = 31), road cyclists (n = 8), swimmers (n = 10), strength/power athletes (n = 9) of similar age (range, 15 to 31 yrs), training experience (4 to 9 years), and age-matched healthy male sedentary controls (n = 15). Absolute interventricular septum (IVS) thickness and LV wall thickness, but not LV diameter, were greater in athletes than sedentary controls. Left ventricular mass of all athletes but relative wall thickness of only BP, swimmers, cyclists, and strength/power athletes were higher as compared with controls (p < 0.05). Among athletes, smaller IVS thickness was observed in MDR than BP, cyclists, swimmers or strength/power athletes, while LDR had higher body size-adjusted LV diameter as compared to BP, cyclists and strength/power athletes. In conclusion, relative LV diameter was increased in long distance runners as compared with basketball players, cyclists, and strength/power athletes. Basketball, road cycling, strength/power, and swimming training were associated with increased LV concentricity as compared with paddling or distance running.